The Effect of Task Tepetition on Complexity, Accuracy, and Fluency of Indonesian Maritime Vocational School Students’ Speaking Performance - Banun Havifah Cahyo Khosiyono (EDULANGUE, 2021)
Developments in the area of task-based language teaching (TBLT) research have focused on the task implementation factors in that they effectively promote successful language performances. The present study aimed to examine the effect of task repetition on the speaking performances of students who studied English Specific Purposes at an Indonesian Maritime Vocational School. To this end, a pre- and post-test quasi-experimental design was applied that involved 43 participants, who were non-randomly selected and considered as two groups of the experimental and control ones. Both groups took a pre-test to ensure their homogeneity in speaking skill. For 12 sessions, the experimental group was engaged in repetitive practice of speaking tasks. Three weeks after the end of the treatment, both groups performed the two post-tests. The results of independent samples t-tests showed that the experimental group significantly outperformed their counterparts in the control group in terms of task complexity on the two post-test phases (p<.05). However, they did not differ significantly in terms of accuracy.